Nonlinear analysis of circular high strength concrete-filled stainless steel tubular slender beam-columns. (1st January 2017) - Patel, Vipulkumar Ishvarbhai; Liang, Qing Quan; Hadi, Muhammad N.S.
Highlights: A fiber-based model for circular high strength CFSST slender columns is proposed. The accurate three-stage stress-strain laws for stainless steels are incorporated. Parametric study on CFSST slender columns with confinement effects is undertaken. The fiber-based model predicts well column deflections and strength envelopes. Abstract: Concrete-filled stainless steel tubular (CFSST) slender columns are increasingly used in composite structures owing to their distinguished features, such as aesthetic appearance, high corrosion resistance, high durability and ease of maintenance. Currently, however, there is a lack of an accurate and efficient numerical model that can be utilized to determine the performance of circular CFSST slender columns. This paper describes a nonlinear fiber-based model proposed for computing the deflection and axial load-moment strength interaction responses of eccentrically loaded circular high-strength CFSST slender columns. The fiber-based model incorporates the accurate three-stage stress-strain relations of stainless steels, accounting for different strain hardening characteristics in tension and compression. The material and geometric nonlinearities as well as concrete confinement are included in the computational procedures. Existing experimental results on axially loaded CFSST slender columns are utilized to verify the proposed fiber-based model. A parametric study is conducted to examine the performance of high-strength slender CFSST beam-columns with various geometric and material parameters. It is shown that the fiber-based analysis technique developed can accurately capture the experimentally observed performance of circular high-strength CFSST slender columns. The results obtained indicate that increasing the eccentricity ratio, column slenderness ratio and diameter-to-thickness ratio remarkably decreases the initial flexural stiffness and ultimate axial strength of CFSST columns, but considerably increases their displacement ductility. Moreover, an increase in concrete compressive strength increases the flexural stiffness and ultimate axial strength of CFSST columns; however, it decreases their ductility. Furthermore, the ultimate axial strength of CFST slender columns is found to increase by using stainless steel tubes with higher proof stresses.